Evaluation of Differences in Metabolic and Immunologic Markers and Cardiovascular Risk in hiv-1 Patient (2021)
ABSTRACT: Introduction: hiv infection induces an exacerbated chronic inflammatory response, which triggers met abolic disorders and cardiovascular diseases; however, there are individuals, known as hiv controllers, who do not have typical progression markers. As cardiovascular risk tests are not accurate on hiv-1 infected patients, the study of metabolic and inflammatory parameters in individuals with different patterns of progression could contribute to the definition of predictors of cardiovascular disease in this population. The aim of this study was to compare hiv controllers and hiv progressors (with and without antiretroviral therapy) as well as with healthy controls in order to explore differences and correlations in metabolic and inflammatory biomarkers associated with cardiovascular risk. Materials and methods: This was a cross-sectional analytical study which included 63 individuals infected with hiv-1 classified as hiv controllers or progressors (with or without antiretroviral therapy), and a healthy control group. The following parameters were determined: carotid intima-media thickness (cimt); cardiovascular risk scores; lipid profile, fasting glucose, high-sensitivity crp, D-dimer, sCD14, sCD163, il-6, and il-18. Data were compared with Anova or Kruskal–Wallis, and correlations were evaluated by the Spearman coef ficient. Results: While there were no significant differences in Framingham, dad or cimt values, hiv con trollers exhibited lower triglycerides levels when compared with hiv progressors. No differences were observed in markers, such as high-sensitivity crp, il-6, il-18, and sCD163, among the groups. The median hdl value was higher in hiv progressors on antiretroviral therapy, and cimt in hiv controllers was nega tively correlated with sCD14. Conclusion: hiv controllers have a different cardiovascular profile than hiv progressors according to their values in metabolic and immunological biomarker.